Regulatory challenges for biological control - Hoeschle-Zeledon, Irmgard; Neuenschwander, Peter; Kumar, P. Lava (2013)
Biological control is a significant component of integrated pest management programs around the world. However, uncertainty about the risk of unanticipated effects on non-target organisms is one of the major concerns surrounding the release of biological control agents. This Brief has been prepared with the intention of: • aiding scientists within the CGIAR, national programs and universities who develop, adopt or promote biological methods to control pests, pathogens and weeds; • informing about the legal requirements in different countries for the import, release and commercialization of these agents; and • increasing understanding among decision-makers in regulatory agencies of the risks and benefits associated with biological control programs. This document also provides a list of various biological control agents adopted in different countries, as well as those currently under development, as a ready reference to new users. Biopesticides composed of non-living ingredients like plant products (e.g. neem extracts) or genetically modified organisms (GMOs) are not considered in this review. It is hoped that this document will facilitate the harmonization of regulatory procedures for import, production and release of biological control agents across countries in developing regions of the world and enable rapid interventions in situations of pest invasion and outbreak. This in turn will stimulate further research towards alternatives to chemical pest control methods, through biological control or the development and large scale application of readily available products, to the benefit of farmers, the environment, and society as a whole.